TESTING THE RELATIONSHIPS BETWEEN ENERGY PRICES AND THE BORSA ISTANBUL INDICES - Mehmet Eryiğit; Faruk Temel (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Oil and natural gas which are the most used energy sources are consumed as raw materials in many fields. The development of technology and population increase makes these energy sources important for financial markets and the overall economy. Turkey, energy importing and developing country, may be influenced intensely by changes in energy prices. In this study, long-term and short-term relationships between energy prices and Borsa Istanbul indices using daily data between 01.01.2007-31.10.2017 were examined by Johansen cointegration, vector autoregression (VAR), Granger causality tests, and impulse-response functions. The long-term relationship between energy prices and Borsa Istanbul indices was not found. On the other hand, it was concluded that energy prices had positive impacts on Borsa Istanbul indices in the short-term. Furthermore, oil prices Granger cause natural gas prices, Food Beverage, and Chemical Petrol Plastic indices.